2022
DOI: 10.3390/nano12071127
|View full text |Cite
|
Sign up to set email alerts
|

Direct Laser Writing of Copper Micropatterns from Deep Eutectic Solvents Using Pulsed near-IR Radiation

Abstract: In this study, we developed a method for the fabrication of electrically conductive copper patterns of arbitrary topology and films on dielectric substrates, by improved laser-induced synthesis from deep eutectic solvents. A significant increase in the processing efficiency was achieved by acceptor substrate pretreatment, with the laser-induced microplasma technique, using auxiliary glass substrates and optional laser post-processing of the recorded structures; thus, the proposed approach offers a complete man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Subsequently, a 1 mm thick layer of DES was applied to the substrates. Previously, it was found that placing an auxiliary glass slab onto the DES layer to create a “sandwich” sample was effective for laser-induced synthesis in DES . In this study, the same design was used for borosilicate glass, PI, and fiberglass plastic.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, a 1 mm thick layer of DES was applied to the substrates. Previously, it was found that placing an auxiliary glass slab onto the DES layer to create a “sandwich” sample was effective for laser-induced synthesis in DES . In this study, the same design was used for borosilicate glass, PI, and fiberglass plastic.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of this procedure can be found elsewhere. 45 Fiberglass plastic and PTFE substrates were structured using 320 P sandpaper (Ra ∼ 7 μm). The alternative technique was chosen as the materials are not optically transparent for the wavelength used and the LIPAA method cannot be realized.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in that work, CW laser was applied and in the treatment of polymer materials, a significant temperature effect led to melting or graphitization of the surface. In [45] an effective solution for metallization of glass surfaces was achieved by using a commercially available MiniMarker-2, however, the applicability of the developed methods for wider substrate materials range remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The method is based on the photochemical decomposition of the metal-containing precursor under laser irradiation, followed by reduction of the metal and the formation of NPs [ 31 ]. As possible precursors, an extensive list of laboratory-synthesized and commercially available compounds were successfully demonstrated, such as organometallic complexes, inorganic, and organic salts [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. It was found that LID allows the user to control the coating density, morphology, and composition of the MNPs deposited on the substrate’s surface.…”
Section: Introductionmentioning
confidence: 99%